A gist on an obscure neoplasm in Ghana: gastrointestinal stromal tumours - Joseph Yorke; Samuel Gyasi Brenu; Ronald Awoonor-Williams; Stephen Tabiri; Anwar Sadat Seidu; Francis Akwaw Yamoah; Joseph Akpaloo; Edmund Muonir Der; Ernest Adjei; Isaac Okyere; Kenneth Kelechi Ihekanandu; Ernest Bawuah Osei Bonsu; et al. (BMC Research Notes, 2023)
Abstract Background Gastrointestinal Stromal Tumour is a rare but potentially curable tumour of the gastrointestinal tract accounting for up to 1% of all gastrointestinal tumours. The discovery of Imatinib mesylate, a novel tyrosine kinase inhibitor has improved the chances even for unresectable, recurrent, or metastatic diseases. Methods This study sought to document the clinical and pathological characteristics of GISTs from two tertiary hospitals in Ghana that have undergone immunohistochemistry confirmation between 2014 and 2021. Results The median age of the subjects was 50 years with most of them (28.0%) being above 61 years. There were more females than males (64.0% vs. 36.0%). Abdominal mass and abdominal pain made up the majority of the clinical presentations. The majority of the subjects had partial gastrectomy (32.0%) which was followed by wedge resection (28.0%). Appendectomy and sleeve gastrectomy were the least performed procedures (8% each). Four of the 25 patients (16.0%) had resections of involved contiguous organs done with splenectomy being the most common procedure. The majority of GISTs were found in the stomach (68.0%) followed by the appendix (12.0%) and small bowel (12.0%). Gastrointestinal bleeding (55.8%) and abdominal pain (38.5%) were the most reported symptoms. Free resection margins were observed in 84.0% of the subjects and only 3/25 (12.0%) experienced tumour recurrence. Conclusion GIST is a potentially curable tumour that once was obscure but currently gaining popularity. Surgical resection offers the hope of a cure for localized disease while targeted therapies is a viable option for recurrent, metastatic, or unresectable tumours.